New museums and the making of culture - Message, Kylie (Oxford ; New York : Berg, 2006)
Illustrated with a range of museums and museum spaces - from MOMA in New York to the reconstruction of Ground Zero, from the National Museum of the American Indian in Washington DC to the Museo Guggenheim Bilbao, this book reveals how the museum evolves as a cross-disciplinary, self-consciously political, and self-reflexive institution.
Keywords: Museums -- Social aspects; Museums -- Political aspects; Museums -- Philosophy